Obstetric Outcome in Teenage Pregnancy in a Free Antenatal Care Setting in Southwest Nigeria - Akadiri, O; Bakare, B; Ajenifuja, KO (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: The study was done to compare the obstetric outcome in teenage pregnancies with that of non-teenage pregnancies in a setting where antenatal care and delivery is free. Methods: A retrospective case control study was conducted at the state specialist hospital Ondo southwest Nigeria between January 1st 2011 to December 31st 2011. The data regarding outcome of all teenagers (13-19) delivering in the hospital was compared with that of selected non-teenagers (20 -35 years) taken as control. Chi-square and student t- test was used with 0.05 as level of significance. Results: There were a total of 3054 deliveries during the study period. Incidence of teenage pregnancy was 4.0% (n=122) with a mean age of 18years. Teenagers were more likely to have anaemia and malaria in pregnancy but less likely to have antepartum haemorrhage and preeclampsia. Teenagers are more likely to have spontaneous vagina delivery compared to non-teenagers. The perinatal outcome did not differ significantly. Conclusions: The majority of the teenagers were nulliparous and most delivered spontaneously by the vaginal route. They are more likely to have instrumental delivery and less likely to have preeclampsia compared to older patients though this was not statistically significant.